2018
DOI: 10.1681/asn.2017121265
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract

Abstract: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 69 publications
(59 reference statements)
9
149
0
1
Order By: Relevance
“…The diagnostic yield was 17.0% in CAKUT which is close to the reports from an international cohort. 14 17 The diagnostic yields by trio-WES were superior, especially in renal tubular disease and renal calcinosis of our cohort. A significantly higher proportion of de novo mutations were detected early in trio-WES compared with TGS or singleton-WES which could be the limitation of the single patient-based approach, where de novo mutations are confirmed only after segregation.…”
Section: Discussionmentioning
confidence: 65%
“…The diagnostic yield was 17.0% in CAKUT which is close to the reports from an international cohort. 14 17 The diagnostic yields by trio-WES were superior, especially in renal tubular disease and renal calcinosis of our cohort. A significantly higher proportion of de novo mutations were detected early in trio-WES compared with TGS or singleton-WES which could be the limitation of the single patient-based approach, where de novo mutations are confirmed only after segregation.…”
Section: Discussionmentioning
confidence: 65%
“…The genetic diagnosis rate of 13.8% is similar to previous studies employing various detection methods. TES achieved a 1-6% positive result in patients with several types of CAKUT [16,17], while whole exome sequencing (WES) studies found causative mutations of known CAKUT genes in 11-14% of patients [14,15,21] and mutations of novel genes in 8% of families [14]. Previous CNV studies reported that 4.5-16.6% of patients with variable CAKUT were carrying pathogenic CNVs [11][12][13]18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains challenging because of genetic and phenotypic heterogeneity and incomplete penetrance of CAKUT. In the literature, diagnostic yield of genetic testing of patients with CAKUT is approximately 5-20%, representing either single nucleotide variants (SNVs) or CNVs of the relevant genes [11][12][13][14][15][16][17][18][19]. Most of the large studies on CAKUT are from Western countries, therefore genetic background of CAKUT in Asian populations is yet to be elaborated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this mapping, it was hypothesized that a biallelic gene mutation residing within a homozygous peak region caused the subject's renal disease. To identify the most probable disease-causing mutation, we used the following criteria for exome 7. variant filtering [40][41][42][43] : (1) exclusion of all variants that did not change the amino-acid sequence or affected canonical splice sites (defined as ± 6 nucleotides surrounding the exon-intron boundary),…”
Section: A Case Of Human Arpkd Associated With Homozygous Cys Mutationmentioning
confidence: 99%
“…Mutation calling was performed in line with proposed guidelines, 41 and the following criteria were employed as previously described 42,43 . The variants included were rare in the population with mean allele frequency <0.1% and with 0 homozygotes in the adult reference genome databases ExAC and gnomAD.…”
Section: Whole Genome Sequencing and Mutation Callingmentioning
confidence: 99%